Development of metal phosphate incorporated polyaniline electrodes for supercapattery / Fatin Saiha Omar - Fatin Saiha , Omar (2018)
As the demand for green and sustainable energy increases, the advantages of high power density, instantaneous charge and discharge capabilities as well as long life span have made supercapacitor as one of the important device for energy storage and power supply management. Nevertheless, one of the main issues is their low energy density which has limit the employment of supercapacitors in broader applications. To address this issue, developing electrode materials that are efficient, cost-effective, tunable and have high surface area is an appealing alternative to boost the performance of supercapacitor (i.e. capable to store high charge and yet undergo minimal decayed during prolong life cycle). Herein, this work is reported on the synthesis of electrode materials and their relationships with supercapacitor performance. In this study, different nanostructures and morphologies of nickel phosphate Ni3(PO4)2 have been prepared by sonochemical method followed by calcination (with different calcination temperatures). The crystallinity, purity, morphology and surface area of Ni3(PO4)2 were authenticated by X-ray diffraction (XRD), fourier transform infrared (FTIR), field emission scanning electron microscopy (FESEM) and X-ray photoelectron spectroscopy (XPS) analysis. The electrochemical performances such as specific capacity, rate capability and electrical conductivity of the synthesized materials were studied through cyclic voltammetry (CV), galvanostatic charge-discharge (GCD) and electrochemical impedance spectroscopy (EIS) techniques. It was observed that the amorphous structure of Ni3(PO4)2 renders in high specific capacity (539 C/g at the current density of 1 A/g)) mainly because of its highly porous structure that augmented the electroactive sites for redox reaction. Nevertheless, it exhibited low rate capability due to its poor electrical conductivity which motivated the incorporation of Ni3(PO4)2 with silver (Ag) ions to form binary composite of nickel phosphate-silver phosphate nanocomposite (Ni3(PO4)2-Ag3PO4). Ni3(PO4)2-Ag3PO4 was prepared by fixing the amount of Ag precursor with various mass of Ni3(PO4)2. Crystalline structure of Ag3PO4 nanoparticles were found to be intimately decorated on the surface of Ni3(PO4)2 and had significantly improved the rate capability of the host Ni3(PO4)2 from 29 to 78 % of capacity retention. Unfortunately at low current rate, the specific capacity achieved by Ni3(PO4)2-Ag3PO4 was lower than that of Ni3(PO4)2 with the specific capacity of 478 C/g at 1 A/g. Ni3(PO4)2-Ag3PO4 was further blended with polyaniline (PANI) (synthesized by chemical oxidative polymerization of aniline monomer) without any binder to form tertiary composite of polyaniline-nickel phosphate-silver phosphate (PANI-Ni3(PO4)2-Ag3PO4). The specific capacity shown by PANI-Ni3(PO4)2-Ag3PO4 was increased to 677 C/g at 1 A/g with the rate capability of 76 % capacity retention. Overall, the improved performance displayed by PANI-Ni3(PO4)2-Ag3PO4 electrode is attributed to (i) the utilization of the surface area from each material for the effective redox reaction, (ii) the presence of Ag3PO4 nanoparticles which increased the electrical conductivity and (iii) tubular shape of conductive PANI that support Ni3(PO4)2-Ag3PO4, providing the interconnected paths for quick electron transfer rate and preventing closely packed of Ni3(PO4)2-Ag3PO4 particles. For real application, PANI-Ni3(PO4)2-Ag3PO4 was fabricated into hybrid supercapacitor (PANI-Ni3(PO4)2-Ag3PO4//activated carbon) and obtained energy density of 38.9 Wh/kg at 400 W/kg with 88 % capacity retention after 5000 cycles.